Recent studies on enzyme application in animal feeding - Francesch M.; Pérez-Vendrell A.M. (Feed manufacturing in Southern Europe: New challenges, 1997)
The addition of enzymes to poultry diets became established commercially during the 1980s. The inclusion of non-starch-polysaccharide-degrading enzymes (NSPDE) in monogastric diets has allowed a higher use of cereals different from maize - mainly barley and wheat, which have significant levels of antinutritive factors such as Beta-glucans and pentosans. However, an accurate utilisation of these enzymes requires the knowledge of the main activities present and their amounts in the preparations and in finished feeds, their stability, and the effects that these enzymes produce on productive and physiological parameters. Several trials have been conducted in our Department using some commercial enzymes in barley based diets for broilers chicks and laying hens. Later, the studies were directed to study the use of enzymes in laying hens, where the effect of enzymes were less clear and more controversial. Finally, experiments were planned to elucidate the effect of high-viscosity diets and enzyme addition on some physiological parameters, such as digesta viscosity, rate of feed passage, endogenous digestive enzymes, survival of Beta-glucanases in the digestive tract and ileal nutrient digestibility. Additionally, analytical procedures to evaluate the activities present in the commercial enzymatic products, in feeds and their stability to technological processes and storage conditions have been developed. All these methods are presented and discussed here.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)